Seminar Parenting: Menghadirkan Kebahagiaan Di Rumah: Mempraktikkan Joyfulness Dalam Kehidupan Sehari-Hari - Nurul Jamiah Sidiq; Rika Kurnia R; Muhammad Yusri Bachtiar; Delvhina Manga; Tri Sugiarti M Bakri (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Seminar on "Bringing Happiness into the Home: Practicing Joyfulness in Daily Life" was organized to provide participants, especially parents, with an understanding and practical skills to create a joyful atmosphere at home through the principles of joyfulness. This seminar aimed to equip participants with insights into the importance of happiness within the family and practical ways to strengthen relationships among family members. The methods used in this seminar included lectures, interactive discussions, practical exercises, and role-playing, designed to give participants direct experience in understanding and practicing the concept of joyfulness. The seminar results showed that 90% of participants had a good understanding of the importance of joyfulness and were ready to implement its principles in their lives. However, the main challenge faced was maintaining consistency in applying positive habits in daily life, especially amidst busy schedules and routines. This seminar also emphasized the importance of effective communication within the family and collaboration between parents and educators in creating an environment that supports family happiness. Overall, the seminar successfully provided a positive impact on participants by enhancing their understanding and skills in fostering happiness at home. With continuous commitment and the application of positive habits, participants are expected to build a harmonious, happy, and loving family.